Changes in pediatric tracheostomy tubes exposed to home dishwashing. (September 2017) - Smolar, David E.; Ho, Brian; Kent, Steven M.; Hughes, C. Anthony; Mettenburg, Donald; Rueggeberg, Fredrick A.; Groves, Michael W.
Abstract: Objective: Determine the effects of household dishwashing on Tracheostomy Tube safety. Introduction: Tracheostomy tubes accumulate biofilms, which may limit their lifespan. Frequent cleaning of the tubes is a method for biofilm prevention. Cleaning practices vary widely. Some families prefer dishwashing of tubes, but its effects are currently unknown. We hypothesize that dishwashing has no significant effect on the physical properties of tracheostomy tubes and can be recommended as a safe way to clean tracheostomy tubes. Methods: Twenty 4.0 Shiley™ pediatric tracheostomy tubes were randomly assigned into dishwashed (DW) and non-dishwashed (NDW) groups, 10/group. DW tubes were subjected to 12 wash cycles. Each tube's hardness along with the surface spectra were analyzed to assess for chemical composition changes. Three cannula samples from each group were also randomly assessed with scanning-electron microscopy and scored by blinded examiners to assess for changes in surface heterogeneity. Results: Hardness testing revealed a statistically significant difference (p = 0.0009) between the NDW and the DW group indicating increased fragility in the dishwashed tubes. Spectral analysis revealed loss of plasticizers, indicating decreased flexibility. Blinded electron microscopy scoring revealed increased surface heterogeneity in the DW group (p = 0.00007). Conclusion: A significant decrease in tube hardness and increased surface heterogeneity were found with dishwashing. The spectral analysis demonstrated increasing fragility. We believe these effects could potentially lead to decreased mechanical safety. With increased surface heterogeneity there is a greater potential for biofilm formation. At this time, dishwashing cannot be recommended as a tracheostomy tube cleaning method.